1993
DOI: 10.1159/000171396
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Epidermal Growth Factor, Transforming Growth Factor Alpha and Their Receptor in Gastro-Oesophageal Diseases

Abstract: This article is a review of aspects of the expression of the regulatory peptides; epidermal growth factor (EGF), transforming growth factor alpha (TGF-α), and their receptor (EGF-R) in the epithelium of the human oesophagus and stomach in health and disease. It has become clear that TGF-α has increased expression in metaplastic, dysplastic and neoplastic tissue of the oesophagus compared with normal mucosa. The degree of abnormal expression becomes more marked as dysplasia increases. TGF-α expression is also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
1
21
0
3
Order By: Relevance
“…It has been reported that EGFR is commonly overexpressed in oesophageal carcinoma (14). Variable but detectable levels of EGFR were observed in all 9 oesophageal carcinoma cell lines used in this study (Fig.…”
Section: Microtubule Destabilising Drugs Decrease Egfr Phospho Rylatisupporting
confidence: 54%
See 1 more Smart Citation
“…It has been reported that EGFR is commonly overexpressed in oesophageal carcinoma (14). Variable but detectable levels of EGFR were observed in all 9 oesophageal carcinoma cell lines used in this study (Fig.…”
Section: Microtubule Destabilising Drugs Decrease Egfr Phospho Rylatisupporting
confidence: 54%
“…Thus, there is an urgent need to improve current therapies. In oesophageal carcinoma patients, EGFR has been reported to be commonly overexpressed (14) and the overexpression is correlated to lymph node metastasis, vascular invasion and shorter survival (15)(16)(17). The EGF and TGF ligands function as mitogens for oesophageal tumour cells (18) and activation of EGFR signalling has been implicated in metastasis via modulation of cell adhesion, angiogenesis, invasion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Although EGF is also expressed in BE, the expression of EGF does not discriminate between dysplastic and neoplastic epithelium. 110 Overexpression of EGFR in the esophagus correlated with the degree of mucosal dysplasia and the occurrence of adenocarcinoma, suggesting that high expression levels may reflect increased malignant transformation potential in BE. 25,110 -112 Al-Kasspooles et al 113 found EGFR gene amplification in 30% of the esophageal adenocarcinomas and also in Barrett's metaplasia, but no correlation with the level of EGFR expression by immunohistochemistry.…”
Section: Growth Factors and Their Receptorsmentioning
confidence: 99%
“…TGF-␣ expression is increased in metaplastic, dysplastic, and neoplastic tissue of the esophagus compared with normal mucosa. 110 The degree of abnormal expression becomes more marked as dysplasia increases and correlates with the proliferative indices in BE. 22,110,114 In summary, EGF/TGF-␣ and their receptor EGFR are important in the progression of normal esophageal squamous epithelium to metaplasia, dysplasia, and finally carcinoma and may be associated with autocrine growth regulation in normal gastrointestinal mucosa and neoplasia.…”
Section: Growth Factors and Their Receptorsmentioning
confidence: 99%
“…EGFR is often overexpressed in esophageal cancers, both squamous cell carcinoma and adenocarcinoma, which in certain cases also express the ligands EGF or transforming growth factor ␣ (TGF-␣), establishing autocrine growth-promoting loops [11][12][13][14][15][16][17][18][19][20]. In fact, EGFR overexpression has been demonstrated to correlate with poor prognosis [16,[21][22][23][24]].…”
Section: The Role Of Egfr In Esophageal Cancermentioning
confidence: 99%